2013
DOI: 10.7763/ijmmm.2013.v1.55
|View full text |Cite
|
Sign up to set email alerts
|

Search for Electrospun Nanofiber Materials Matching The Mechanical Properties of Native Aortic Valve

Abstract: Abstract-Porous electrospun nanofiber materials are very promising as matrixes for heart valve tissue engineering. The perfect material for this purpose has to be both mechanically strong and deformable at the same time.Materials from gelatin, polyurethane (PUR), polylactic acid (PLA) and polycaprolactone (PCL) made in several density variants were analyzed using uniaxial tensile tests and compared to mechanical properties of porcine aortic valve (AV) leaflets in radial and circumferential directions.In circum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Since the authors of this article have previous experience with production and processing of PCL nanofibers (see Figure ), this will be used to illustrate general problems related to the fabrication of nanofibers. First of all, the nanofibers patches are much weaker in comparison to native tissues, for example, elasticity (E), ultimate stress (σ M), and ultimate strain (σ X) for PCL nanofibers patch (15.7 g m −2 ) are 1.3 ± 0.2 MPa, 0.3 ± 0.05 MPa, and 37.9% ± 2.46% respectively, while for porcine aortic valve the values reach 9.7 ± 1.3 MPa, 2.3 ± 0.6 MPa, 44.8% ± 5.9%, respectively . Additionally, for anisotropic PCL mats the elasticity can be significantly lower (even sometimes being a few folds lower in magnitude) on the direction perpendicular to the alignment direction.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since the authors of this article have previous experience with production and processing of PCL nanofibers (see Figure ), this will be used to illustrate general problems related to the fabrication of nanofibers. First of all, the nanofibers patches are much weaker in comparison to native tissues, for example, elasticity (E), ultimate stress (σ M), and ultimate strain (σ X) for PCL nanofibers patch (15.7 g m −2 ) are 1.3 ± 0.2 MPa, 0.3 ± 0.05 MPa, and 37.9% ± 2.46% respectively, while for porcine aortic valve the values reach 9.7 ± 1.3 MPa, 2.3 ± 0.6 MPa, 44.8% ± 5.9%, respectively . Additionally, for anisotropic PCL mats the elasticity can be significantly lower (even sometimes being a few folds lower in magnitude) on the direction perpendicular to the alignment direction.…”
Section: Introductionmentioning
confidence: 98%
“…The electrospun and jet‐sprayed fibers have already been proved to have the potential for engineering a functional heart‐valve, but the final goal of delivering functional structure for clinical applications has not been accomplished yet. Perhaps it is due to limitation of nanofibers materials and its fabrication process.…”
Section: Introductionmentioning
confidence: 99%
“…Flexion fatigue is thought to be one of the main causes of leaflet rupture [36,42]. Arcidiacono and colleague [1] with means of computer modeling have shown that even the slightest differences in rigidity of valve leaflets have an impact on the dynamics of valve opening and closure, stressing the importance of leaflet mechanical properties homogeneity within one valve. All these previous studies point out that increased leaflet rigidity characterized by higher modulus of elasticity values may have significant impact on bioprosthesis longevity and hemodynamic properties.…”
Section: Potential Influence Of Mechanical Properties Of Bioprosthetic Valve Leaflets On Their Longevitymentioning
confidence: 99%